Impact of Forest Fires on Micronutrients on Peat Soils in Rimbo Panjang Kampar Regency - Ervina Aryanti; Sevi Dwi Adiya; Novita Hera (Jurnal Biologi Tropis, 2023)
Forest fires that occur on peat soils can change the chemical properties of the soil, including the abundance of micronutrients. The aims of this study was to compare micronutrients on unburned peat soil and one year after a fire in a peat soil conservation forest area in Rimbo Panjang, Kampar Regency, Riau Province. The study was conducted from October to December 2020. This study used an observation method. Data processing was analyzed using an Independent Sample T-test. The data testing parameters analyzed in the laboratory include pH, Fe, Cu, Mn, and Zn. The results showed that there was an increase in Fe micronutrients (11.33 to 31.87) in peat soils 1 year after the fire, while in other nutrients (Cu, Mn and Zn) and pH did not increase.